The Improvisation of Power and Shakespeare’s Second Tetralogy: A Greenblattian Approach - Azita Zamani; Zahra Bordbari; Javad Yaghoobi (Critical Literary Studies)
The current research examines Stephen Greenblatt’s theories on the improvisation of power as well as tyranny in William Shakespeare’s second tetralogy to investigate the complex network of non-violent psychological domination of human being’s mind, by the manipulation of symbolic order through the stages of displacement and absorption. It examines how the Western psychic mobility and its embodiment in empathy and the improvisation of power affect the represented English society in the Medieval era and how the consequential power relationships impact on the ways of ruling the country. The improvisation of power deconstructs the vertical and hierarchical power relations and makes them more diagonal, horizontal or even upward. The represented Medieval English court is a dark labyrinth of conspiracy, intrigue, treason, and complicity. This duality roots in religious fundamentalism of Roman Catholic church. The tension between the two paradigms of court and church causes turbulence and chaos. The result is the absolute submission of the majority through the improvisation of power, which paves the ground for the Machiavellian minority to exert power and gratify their personal self-interest-driven plans, which are mostly tyrannical. Through the improvisation of power, the course of history could change.